Awareness Cybercrime Phishing Email Menggunakan Secure Socket Layer Sebagai Interpretasi Information Security - Kotim Subandi; Dinar Munggaran Ahmad; Victor Ilyas Sugara; Adriana Sari Aryani; Hermawan (Prosiding Seminar Nasional Teknoka, 2024)
Email phishing is a fraudulent technique used by cybercriminals to obtain sensitive information through emails that appear legitimate but have malicious purposes. Information security has become a crucial aspect in the increasingly developing digital world, especially along with the increasing threat of cybercrime, such as email phishing. In this context, implementing Secure Socket Layer (SSL) is one solution to increase awareness and mitigate risks against phishing attacks. SSL, which is a security protocol for data encryption, can help protect digital communications by authenticating servers and encrypting data sent, thereby reducing the potential for misuse of personal data sent via email. This research aims to examine the role of SSL in providing protection against email phishing and increasing user awareness regarding the importance of information security in the use of digital technology. Through an information security interpretation approach, this study suggests that SSL can serve as an effective barrier in reducing the risk of phishing attacks and increasing the level of user trust in the emails received. Therefore, it is important for individuals or organizations to understand and apply information security principles such as the use of SSL to maintain the integrity and confidentiality of data exchanged online.